The effects of in-barrel moisture on extrusion parameters, kibble macrostructure, starch gelatinization, and palatability of a cat food - Baller, Mayara A. [UNESP]; Pacheco, Peterson D.G. [UNESP]; Peres, Francine M. [UNESP]; Monti, Mariana [UNESP]; Carciofi, Aulus C. [UNESP] (Elsevier, 2018)
Water addition is required for proper extrusion, improving dough flow, starch hydration and swelling, viscosity generation, and extrudate cellular formation. The implications of changing in-barrel moisture, however, is little studied for cat foods. Using a nutritionally balanced cat food recipe, the present study evaluated the application of six amounts of water at the extruder barrel, obtaining the following mass in-barrel moistures: 220 g/kg, 270 g/kg, 300 g/kg, 320 g/kg, 350 g/kg, and 370 g/kg. Treatments were processed in a single screw extruder; after stabilization (45 min), extrusion parameters was recorded at each 15 min, with four samplings per moisture level (considered the experimental unit). Treatments were evaluated in a sequential addition of moisture, and results submitted to variance analysis and compared by polynomial contrasts (P < 0.05). The specific mechanical energy application, temperature and pressure of extrusion, starch gelatinization, and in vitro digestibility of organic matter decreased with increasing in-barrel moisture (P < 0.01). The difference between reactive to total lysine decreased with increased in-barrel moisture, showing less lysine complexation with higher moisture contents (P < 0.05). Kibble expansion and lipid complexation showed a quadratic response (P < 0.01), with higher values for in-barrel moistures between 280 g/kg to 320 g/kg. Cat preferences to foods did not change due to water addition during extrusion. In-barrel moistures between 280 g/kg and 320 g/kg is suggested to improve extrudate formation, allow high starch gelatinization, and control mechanical energy application to the mass.
Keywords: Felines; Lipid complexation; Lysine; Mechanical energy